Análise econômica da produção de biodiesel em pequena unidade de processamento empregando óleos residuais como matéria-prima - Fantinel, Antonio Luiz (2016)
Biodiesel is classified biodegradable fuel derived from renewable sources such as vegetable oils, pure or not and animal fats, in the presence of an alcohol (methane/alcohol) and catalyst (base, acid or enzyme), through the process of Transesterification. Between the various raw materials of triglyceride used in biodiesel production, little has given attention to the residual oil (OGR) from domestic and industrial disposal after its use in cooking food processes. However, show gains, economic and environmental technicians with the use of biodiesel production residue, reducing considerably the costs of raw materials, which represent almost 80% of the total cost of production when used soybean oil, making himself impossible economically for small biodiesel production units. These observations emerged from the purpose of this research, which aims to assess the economic and environmental viability of biodiesel production in a small industrial unit, employing residual oils and fats (OGR) as raw material. For support of this investigation, a field research in a small biodiesel production unit installed in the Park of exhibitions of the tobacco growers Association of Brazil-AFUBRA for biodiesel production. As a tool for determining, the methodology used economic activity-based costing (ABC). With processing has been found that the small biodiesel production unit presented 97.6% yield, being produced 612 liters of biofuel with conversion rate at 99% esters for Molar ration Methanol/oil 4:1 and 3% of sodium Methoxide as catalyst. Under the economic point of view, the final cost of a liter of biodiesel production, without taxes, was 0.82 R$ (82 cents) of whom 46.8% corresponds to the contribution of the processing and 43.2% with purchase of raw material. Through the ABC methodology it was noted that one of the six activities the process consumes resources is Transesterification, followed by preparation of raw materials, purification. Already the activity with less representation on the cost of processing for biodiesel production was heating the raw material. Between these environmental benefits with the implementation and operation of small production units quotes not to use drinking water to step current purification of biodiesel, and the reuse of this highly polluting waste, thus avoiding the contamination of rivers, lakes and the blocking of sewer networks. Such initiatives support the development of new alternatives linked to the renewable economy, seeking to transform the unsustainability in sustainability.